1995
DOI: 10.1002/ijc.2910630611
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of K‐ras mutations in normal appearing lung tissues and sputum of patients with lung cancer

Abstract: To evaluate the possible use of mutant ras as a biomarker for lung cancer, we have analyzed "normal appearing" lung tissue, lung tumor, lung metastases and sputum samples from patients with non-small cell lung cancer (NSCLC). As a control, we used lung tissue and sputum samples from patients without oncological diseases or lung disorders. Our analyses were performed with the aid of enriched PCR (EPCR), a method which enables detection of ras mutation even if present at low incidence. EPCR identified K-ras codo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 13 publications
1
44
0
Order By: Relevance
“…Previously, we detected a mutant KRAS gene (codon 12) in case no. 6 out of 30 analysed (Yakubovskaya et al, 1995). The findings indicate high genetic instability of this tumour.…”
Section: Microsatellite Instabilitymentioning
confidence: 76%
“…Previously, we detected a mutant KRAS gene (codon 12) in case no. 6 out of 30 analysed (Yakubovskaya et al, 1995). The findings indicate high genetic instability of this tumour.…”
Section: Microsatellite Instabilitymentioning
confidence: 76%
“…As early as 1989, Slebos et al have identified that the KRAS mutation status can be used for lung cancer detection or prognosis prediction (Slebos & Rodenhuis, 1989). In 1995, Yakubovskaya et al detected 12 different KRAS mutations in nearly 60% of tissue specimens of non-small cell lung cancer (NSCLC) patients (Yakubovskaya et al, 1995). As for pancreatic, stomach and breast cancers, there have been a number of studies reporting KRAS mutations (Smit et al, 1988;Gocke et al, 1997;Deramaudt & Rustgi, 2005;Carstens et al, 1988;Lee et al, 2003;Shen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Therefore, molecular study of sputum has been suggested to be more sensitive than cytology in diagnosis of lung cancer. [6][7][8][9][10] For instance, hypermethylation of p16 gene was found in sputum collected from patients with lung squamous cell carcinomas, 5-35 months before sputum cytological and clinical diagnoses. 11 MicroRNAs (miRNAs) are a newly discovered class of small noncoding RNAs that have critical roles in a wide spectrum of biologic and pathologic processes.…”
mentioning
confidence: 99%